ANALISIS SISTEM INFORMASI PERSEDIAAN GREENBEAN DALAM MENINGKATKAN EFEKTIVITAS PENGENDALIAN INTERNAL PADA STARBUCKS PALEMBANG ICON - Paradila, Erika (P3M STIE Mulia Darma Pratama, 2024)
Accounting information systems play a crucial role for both companies and institutions. In a company, having a well-functioning accounting information system is essential, as it should be able to process acquired data into useful information. Internal control is one of the factors that enhance the field of business activities focused on inventory management. Controlling inventory is essential in preventing errors in handling the quantity of goods, issues related to shipping, and transaction data within an interconnected process aimed at achieving profitability. The purpose of this study is to determine the effectiveness of the greenbean inventory information system in enhancing internal control at Starbucks Palembang Icon. The research methodology employed in this study is qualitative descriptive. The findings indicate that the greenbean inventory information system at Starbucks Palembang Icon is implemented by the Standard Operating Procedures (SOP). However, there are still some issues due to non-compliance with SOP, such as occasional shortages of greenbeans and delays in greenbean deliveries. The internal control of greenbean inventory, following the COSO framework, is adequate and aligned with existing theories.